Age at first calving and calving interval of holstein friesian and crossbred holstein friesian: Gir cows - Freitas, Ary Ferreira de; Madalena, Fernando Enrique; Martinez, Mário Luiz (Pesquisa Agropecuaria Brasileira, 2014)
Ages at first calving of 52 Holstein-Friesian (HPB) cows, 69 1/2 HPB: 1/2 Gir (F1) and 66 3/4 HPB: 1/4 Gir (B1) were compared. The animals of all three groups were maintained together in the same herd. Artificial insemination with fresh semen was mainly used, and also natural mating, with HPB bulls for HPB and F1 cows, and F1 bulls for B1 cows. The model for age at first calving included the effects (fixed) of year-season of birth of cow genetic group and the interaction of both effects. Only genetic group effects were significant (P<0.05). The model for calving interval induded the effect of year and season of calving, genetic group, two and three factor interactions of these effects, and linear and quadratic regression on parity. The season x genetic group interaction was significant (P = 0.05). The relation between interval (E) and parity (N) was described by the equation E = 576.21-41.23 N + 4.83 N2, indicating that the minimum interval was attained at the 4th calving.